2015
DOI: 10.1137/140982015
|View full text |Cite
|
Sign up to set email alerts
|

Sandpiles, Spanning Trees, and Plane Duality

Abstract: Abstract. Let G be a connected, loopless multigraph. The sandpile group of G is a finite abelian group associated to G whose order is equal to the number of spanning trees in G. Holroyd et al. used a dynamical process on graphs called rotor-routing to define a simply transitive action of the sandpile group of G on its set of spanning trees. Their definition depends on two pieces of auxiliary data: a choice of a ribbon graph structure on G, and a choice of a root vertex. Chan, Church, and Grochow showed that if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Motivated by a question of Ellenberg [19], [28], Baker and Wang proved that if the ribbon structure is planar, then all Bernardi torsors are isomorphic and they respect plane duality [9]. Similar results were proven for rotor routing by Chan et al [15], [16] (see [27] for background on rotor routing). In fact, Baker and Wang showed that the torsors induced by Bernardi bijections are isomorphic to the torsors induced by rotor routing if the ribbon structure is planar.…”
Section: Introductionmentioning
confidence: 75%
“…Motivated by a question of Ellenberg [19], [28], Baker and Wang proved that if the ribbon structure is planar, then all Bernardi torsors are isomorphic and they respect plane duality [9]. Similar results were proven for rotor routing by Chan et al [15], [16] (see [27] for background on rotor routing). In fact, Baker and Wang showed that the torsors induced by Bernardi bijections are isomorphic to the torsors induced by rotor routing if the ribbon structure is planar.…”
Section: Introductionmentioning
confidence: 75%
“…In the guise of "abelian sandpile model", chip-firing games play an important role in the study of self-organized criticality in statistical physics [4,20]. The chip firing game introduced by Baker and Norine is relevant for classical combinatorial problems about graphs, relating to spanning trees [16], the uniqueness of graph involutions [6], and potential theory on electrical network graphs [7].…”
Section: Known Resultsmentioning
confidence: 99%
“…Similarly, define σ * by orienting each simple cycle of the dual graph G * clockwise and composing with the natural bijection between oriented cuts of G and oriented cycles of G * . By [38,Theorem 15], the simply transitive action of Jac(G) on T (G) afforded by Theorem 1.1.2 in this case coincides with the "Bernardi torsor" defined in [8] and a posteriori with the "rotor-routing torsor" defined in [12,13]. In particular, we get a new "geometric" proof of the bijectivity of the Bernardi map.…”
Section: Then the Map T → [O(t )] Is A Bijection Between T (G) And G(g)mentioning
confidence: 89%